LANDSCAPE ELEGANCE: MAGNOLIAS AS THE FOCAL POINT FOR OUTDOOR BEAUTY - Liu, Jing; Chen, Xin (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2023)
Magnolia is a beautiful tree that is known for its large, fragrant flowers, evergreen leaves, and resistance to wind, dust, pollution, and pests. It is native to East Asia and is mostly planted in the region south of the Yangtze River in China. Magnolia has a pure and elegant temperament, signifying the endless life of all things. It is a high-quality greening ornamental tree species, and is commonly used in landscape configuration.